Effectiveness of digital primary prevention interventions targeting physical activity, motor skills and nutrition in children aged 3–10 years in the setting of day care and primary school: protocol for a systematic review. Issue 12 (23rd December 2021) - Timpel, Patrick; Herrmann, Sandra; Flößel, Philipp; Beck, Heidrun; Schwarz, Peter EH
Abstract : Introduction: Available evidence points to an association of increased screen time and the availability of digital tools during childhood with negative health outcomes in later life. For many years, public discourse focused on restricting access and use of digital technologies below certain ages. However, little is known about the specific benefit of a responsible use of digital primary prevention in the setting of (early) childhood education. The objective of this evidence synthesis is to investigate the effectiveness of digital primary prevention interventions targeting physical activity, motor skills and/or nutrition in children aged 3–10 years in day-care facilities and (pre-) schools. Methods and analysis: We present the rationale and methodological steps of a systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses procedures. Automated searches will be conducted by applying a pretested search strategy to the databases MEDLINE/PubMed, EMBASE and PsycInfo to identify relevant interventional (randomised controlled trials, controlled trials, crossover trials and pilot and feasibility) and observational (case–control, cohort) studies in English or German, with no date restrictions. The overall search will be complemented by backward, forward and additional hand searches. Two researchers will independently screen titles/abstracts and assess full texts by applying predefined eligibility criteria. Data extraction will be conducted by using a pretested data extraction sheet. The assessment of methodological quality will be performed independently by two review authors using the Critical Appraisals Skills Programme relevant to the study design applied in the given study. Additionally, qualitative content analysis will be conducted to analyse priorities for future research extracted from the discussion sections and conclusions of included studies. PROSPERO registration number: CRD42020207682.